Employees’ Exposure to Carbon Monoxide in Pakistan Steel Mills - Abid, Kanza; Shams, Zafar Iqbal (International Journal of Environment, 2014)
Many processes in the iron and steel making industries emit carbon monoxide, which causes a variety of toxic effects on human health, such as fatigue, impaired memory, headache, and nausea. At elevated exposure, carbon monoxide poisoning may lead to loss of consciousness and death. Therefore, the current study has been carried out to investigate the occupational exposure of randomly selected fifty-eight employees of Pakistan Steel Mills to the carbon monoxide. The selected employees were from 10 different facilities of the Pakistan Steel Mills, who were working in two different shifts viz. nightshift and dayshift, each of twelve hours. Thirty employees from nightshift and twenty-eight employees from dayshift were monitored for their exposure to carbon monoxide. The instrument was logged to measure the employee’s exposure to carbon monoxide with 1-minute interval. The study reveals that the employees, working in the Raw Materials Production Plant during nightshift were exposed to the highest mean concentration of carbon monoxide while those working in Oxygen Plant during nightshift were exposed to the lowest mean concentration of carbon monoxide. According to study, the highest recorded exposure was found near Blast Furnace during dayshift. The employees’ exposure to 98th percentile concentration of carbon monoxide in different facilities of the steel mills has also been analyzed. The employees’ exposure to carbon monoxide during commuting from home to their workplace has also been investigated.DOI: http://dx.doi.org/10.3126/ije.v3i4.11730      International Journal of EnvironmentVolume-3, Issue-4, Sep-Nov 2014Page: 44-56